TINJAUAN INVESTASI DALAM PERSPEKTIF BUDAYA - Wibowo, Iwan Hari; Muawanah, Umi; Diamastutik, Erlina (Media Mahardhika, 2019)
In the era of development modern world on when this more and more heavy and easy current development technology information, transportation and communication media. Not exception then crossing activities business deliver nation move more and more rapidly and fast rate its development in various form activities, as impact from development the modern world. For example, arrival nation foreign in activities business and investation, with bring their treasures which they have  as the main capital continue discourse for looking for business opportunity in people’s country. Without we realize it they also bring pattern, habit and form culture that will carried away as wrong one default capital. So How if culture that is which also as default capital influence in pattern invest in in country person especially in Indonesia? Will their culture’s   aspect whom they brought as default capital have huge impact on their pattern investation and their business activity in Indonesia? is there the  other factors which will arise post arrival foreign investors  so that affect capital and pattern the investment ?   This kind of issue whom writer wants to raise in this research as a result from research on foreign. Environments in Malang’s PMA form and to get a highlight from entire national’s element, especially for kind of element that has related for environment’s activity, so they will have some cooperative between Government, Investors and our society in solve this issue.